2009
DOI: 10.1136/jech.2009.092296
|View full text |Cite
|
Sign up to set email alerts
|

The effect of influenza vaccination on the incidence of chronic obstructive pulmonary disease exacerbations in the immediate postvaccination period

Abstract: Patients with COPD should be reassured that the influenza vaccination is safe and does not cause an increase in exacerbations. They should be encouraged to take up the vaccination annually before the onset of winter.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 8 publications
1
12
0
1
Order By: Relevance
“…Two studies assessed the occurrence of COPD exacerbations after influenza vaccination compared to either unvaccinated controls [36], or using a self-controlled method consisting of comparing a pre-defined vaccination period with other time periods in the influenza season for each vaccinated subject [37]. Neither study found evidence of an increased risk of exacerbation up to 14 days post-vaccination (Additional file 2).…”
Section: Resultsmentioning
confidence: 99%
“…Two studies assessed the occurrence of COPD exacerbations after influenza vaccination compared to either unvaccinated controls [36], or using a self-controlled method consisting of comparing a pre-defined vaccination period with other time periods in the influenza season for each vaccinated subject [37]. Neither study found evidence of an increased risk of exacerbation up to 14 days post-vaccination (Additional file 2).…”
Section: Resultsmentioning
confidence: 99%
“…In rare circumstances influenza vaccination has been reported to be associated with eosinophilic pneumonia and respiratory failure [105]. Numerous studies have shown no evidence of increased exacerbation risk [103,106,107] and a systematic review conducted in 2017 reported that influenza vaccination confers a "positive benefit-risk ratio" in the COPD population and that existing data supports annual vaccination in patients with COPD [103].…”
Section: Influenza Infection and Copdmentioning
confidence: 99%
“…Acute respiratory infections constitute a major cause of morbidity and mortality globally [1]. According to the updated 2004 World Health Organization (WHO) report, the death toll from acute lower respiratory infections caused by bacterial and viral infections reached 4.2 million and accounted for 7.2% of all deaths worldwide [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…Acute respiratory infections constitute a major cause of morbidity and mortality globally [1]. According to the updated 2004 World Health Organization (WHO) report, the death toll from acute lower respiratory infections caused by bacterial and viral infections reached 4.2 million and accounted for 7.2% of all deaths worldwide [1,2]. Data from the Global Burden of Disease study estimated that the mortality rate from lower respiratory tract infections due to influenza reached 0.9 per 100,000 population in the WHO Middle East and North Africa (MENA) region and the hospitalization rate ranged from 100 to 299 per 100,000 population [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation